Determinants of income security of older persons in Peninsular Malaysia - Sulaiman, Husna; Masud, Jariah (Universiti Putra Malaysia Press, 2012)
This study explored factors determining income security of older Malaysians aged between 55 to 75 years, using a nationwide database on the economic and financial aspects of ageing. The sample comprised 1,841 older respondents in Peninsular Malaysia. Logistic regression analysis was performed (Nagelkerke R Sq. = 0.48) to test the likelihood of selected socio-demographic and economic factors contributing to income security. The results indicated that 53% of the elderly were in the income secure category, earning per capita income above the poverty level. The three strongest predictors were current work, being male and of Malay origin. The findings suggest that income security of older Malaysians can be strengthened by providing work opportunities with decent pay and self-employment opportunities to the elderly in informal urban and rural sectors. Such strategies are of paramount importance to help reduce poverty and vulnerability, increase income security and ultimately the quality of life of the elderly